Let Mia's score be
![x](https://tex.z-dn.net/?f=x)
. Then, Erick scored 10 more than Mia, so his score is
![x+10](https://tex.z-dn.net/?f=x%2B10)
. Isabelle scored 16 less than twice Mia's score, so her score is
![2x-16](https://tex.z-dn.net/?f=2x-16)
. We can see that
![x + x + 10 + 2x - 16](https://tex.z-dn.net/?f=x%20%2B%20x%20%2B%2010%20%2B%202x%20-%2016)
is the sum of these variables, so
the expression represents the total of their scores in this scenario. Moreover, we recall that the variable in the expression,
![x](https://tex.z-dn.net/?f=x)
,
represents Mia's score.To simplify this expression, we add up the variables and the numbers separately, giving us
![x+x+10+2x-16 = (x+x+2x) + (10-16) = 4x-6](https://tex.z-dn.net/?f=x%2Bx%2B10%2B2x-16%20%3D%20%28x%2Bx%2B2x%29%20%2B%20%2810-16%29%20%3D%204x-6)
. Therefore, in simplified form, the expression is equal to
4x - 6. The constant term
in an expression is the term not multiplied by a variable, so in this case, it is
-6.